Filamin A-interacting protein (FILIP) is a region-specific modulator of myosin 2b and controls spine morphology and NMDA receptor accumulation - Yagi, Hideshi; Nagano, Takashi; Xie, Min-Jue; Ikeda, Hiroshi; Kuroda, Kazuki; Komada, Munekazu; Iguchi, Tokuichi; Rahman, Mohammad Tariqur; Morikubo, Soichi; Noguchi, Koichi; Murase, Kazuyuki; Okabe, Masaru; et al. (Nature Publishing Group, 2014)
Learning and memory depend on morphological and functional changes to neural spines. Non-muscle myosin 2b regulates actin dynamics downstream of long-term potentiation induction. However, the mechanism by which myosin 2b is regulated in the spine has not been fully elucidated. Here, we show that filamin A-interacting protein (FILIP) is involved in the control of neural spine morphology and is limitedly expressed in the brain. FILIP bound near the ATPase domain of non-muscle myosin heavy chain IIb, an essential component of myosin 2b, and modified the function of myosin 2b by interfering with its actin-binding activity. In addition, FILIP altered the subcellular distribution of myosin 2b in spines. Moreover, subunits of the NMDA receptor were differently distributed in FILIP-expressing neurons, and excitation propagation was altered in FILIP-knockout mice. These results indicate that FILIP is a novel, region-specific modulator of myosin 2b.